Spectral sensing research for surface and air monitoring in chemical, biological and radiological defense and security applications - Theriault, Jean-Marc; Jensen, James O. (Selected topics in electronics and systems, 2009)
This book provides unique perspectives on the state of the art in multispectral/hyperspectral techniques for early-warning monitoring against chemical, biological and radiological (CB & R) contamination of both surface.